2015
DOI: 10.3928/01913913-20150506-02
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of Vascular Endothelial Growth Factor and Retinopathy of Prematurity

Abstract: The results support the hypothesis that the carrier state of VEGF 634 C/G polymorphism has an impact on the risk of ROP in infants. A broader study may suggest that this marker could be used as an indicator in the screening for ROP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The authors suggested that the correlation of genetic variants in VEGF genotypes with the outcomes of ROP and ROP requiring treatment may be due to linkage disequilibrium with nearby angiogenic genes with unknown genetic variants. Additionally, carriage of the −634C>G allele has been shown to independently increase the risk of BPD and ROP in Japanese and Egyptian neonates, respectively, while the 936CT allele did not ( 30 , 31 ). Although these studies focused on BPD and ROP individually, comparison of these studies highlights the importance of reviews to synthesize research across multiple disease processes.…”
Section: Vegf Polymorphismsmentioning
confidence: 97%
“…The authors suggested that the correlation of genetic variants in VEGF genotypes with the outcomes of ROP and ROP requiring treatment may be due to linkage disequilibrium with nearby angiogenic genes with unknown genetic variants. Additionally, carriage of the −634C>G allele has been shown to independently increase the risk of BPD and ROP in Japanese and Egyptian neonates, respectively, while the 936CT allele did not ( 30 , 31 ). Although these studies focused on BPD and ROP individually, comparison of these studies highlights the importance of reviews to synthesize research across multiple disease processes.…”
Section: Vegf Polymorphismsmentioning
confidence: 97%
“…Genetic association studies with ROP and VEGF gene have been contradictory. 15,33,87,99,142,176,197,206,222,223,305,339,343,381 The Wnt signaling pathway genes previously identified in familial exudative vitreoretinopathy, including FZD4 and LRP5 , and Norrie Disease Protein (NDP) gene have also been explored with positive associations with ROP including stage 4/5 ROP in several studies; 90,97,104,172,173,218,244,342 however, there have been only a few genetic studies with adequate sample size and refined inclusion criteria. A large genetic cohort study identified SNPs in the intronic region of brain-derived neurotrophic factor (BDNF) gene as associated with treatment-requiring ROP, which warrants further studies on functional effects of intronic variants of BDNF and replication studies.…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…indomethacin did not affect the expression levels of the vascular endothelial growth factor system in ductus arteriosus endothelial cells. 7 Several authors investigated vascular endothelial growth factor polymorphisms and their potential association with neonatal morbidities such as bronchopulmonary dysplasia, [10][11][12] retinopathy of prematurity, 8,9 and intraventricular haemorrhage 16 in preterm infants. However, the role of the vascular endothelial growth factor polymorphism rs2010963 on patent ductus arteriosus incidence and treatment success rates has not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 We have recently shown that ibuprofen and indomethacin differentially regulate vascular endothelial growth factor and its receptors in primary endothelial cells of the rat ductus arteriosus. 7 In addition, several studies discussed vascular endothelial growth factor polymorphisms as potential risk factors for several diseases in neonates, including retinopathy of prematurity 8,9 and bronchopulmonary dysplasia. [10][11][12] The aim of the current study was to investigate the incidence of the vascular endothelial growth factor polymorphism rs2010963 status in a large cohort of preterm infants with and without patent ductus arteriosus and its potential association with cyclooxygenase inhibitor treatment success rates.…”
mentioning
confidence: 99%